Current distribution of Achatina fulica, in the State of São Paulo including records of Aelurostrongylus abstrusus (Nematoda) larvae infestation - Ohlweiler, Fernanda Pires; Guimarães, Marisa Cristina de Almeida; Takahashi, Fernanda Yoshika; Eduardo, Juliana Manas (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
The currently known distribution range of Achatina fulica Bowdich, 1822, in the state of São Paulo, Brazil, is presented. The record of A. fulica naturally infested with Aelurostrongylus abstrusus larvae (Railliet, 1898) (Nematoda: Metastrongylidae) can be found in the city of Guaratinguetá. It was found A. fulica with Metastrongylidae larvae without known medical and veterinary importance in the cities of Carapicuíba, Embu-Guaçu, Itapevi, São Caetano do Sul, São Paulo and Taboão da Serra.